Ecotoxicity assesment of antifouling biocide, zinc pyrithione on the Javanese medaka (Oryzias javanicus, Bleeker 1854) - Abdul Aziz, Fatin Zahidah (2017)
Javanese medaka (Oryzias javanicus) has been proposed as a potential model organism for ecotoxicological studies. In recent years, several emerging pollutants have raised concern among scientists. Among others is zinc pyrithione (ZnPT) which is widely used in personal care products and also in agriculture field as fungicide and bactericide. Recently, ZnPT is used in antifouling paints to replace tributyltin (TBT) to prevent attachment of marine fouling organisms on the ship hull. However, limited studies ZnPT could be harmful to non-targeted and early life stage of organisms. Hence, this study aimed to determine the response on the embryological development of Oryzias javanicus and Danio rerio towards different concentration on ZnPT and to investigate the ecotoxicological effects in adults Oryzias javanicus exposed for 21 days to different sublethal concentration of ZnPT exposure. The effects of ZnPT exposure determined via induction of metallothionen (MT), levels of ionic Zn, histological studies, and quantified apoptotic indices. In the first experiment, Oryzias javanicus and zebrafish (Danio rerio) eggs were tested with different ZnPT concentrations to determine its effects on egg's hatchability, median lethal concentration (LC50), embryonic development and deformities. Results showed the ecotoxicological tolerance limit LC50 of ZnPT for Oryzias javanicus was at 8.392 ppb and Danio rerio LC50 was 47.602 ppb. Hatchability of Oryzias javanicus (R = -0.9887) and Danio rerio (R = -0.9577) is inversely correlated with the increase of ZnPT concentration. The Fish Embryo Toxicity (FET) test using different ZnPT concentration showed defects during embryological development, including body malformation and death of embryo. ZnPT also induced a delay in the hatching process, deformation and death of newly hatched larvae. It is desirable that the full life cycle of Oryzias javanicus and Danio rerio to assess the effects of ZnPT chemicals, therefore this studies was a beginning for range finding of NOEC (no observe effect level) and LC50 (median lethal concentration for 50% of sampled animals) in a short-term exposure. Then, median lethal concentration LC50 of adult Javanese medaka was determined via toxicity test for 96hours; the value was 178.23 μg/L. Furthermore, inductions of metallothioneins (MT) and levels of ZnPT were studied for 21 days exposure of adult fish to different concentration of ZnPT. The correlation between ZnPT and metallothinein (MT) in Oryzias javanicus was found statistically significant and positive (R = 0.9541); the ZnPT and MT concentrations in Oryzias javanicus indicated the increasing in ZnPT levels is followed with the increasing of MT levels. The histological examination of the livers, kidney, and gonad of the fish after 21days exposure showed pathological changes and alterations such as of the liver vacuolation; congestion; nodule necrosis, kidney tubule degeneration; glomerulus shrinkage; hemosiderin. Besides, ZnPT caused non-specific in gonad of exposed organisms such as increasing of the atretic follicle, lobular disintegration, reduction of sperm aggregation and etc. Normal histology and immunoperioxidase shown the apoptosis marker in the exposed groups were significantly different (P < 0.05) from the control group. Apoptotic cells were quantified and apoptotic indices were calculated following identification of apoptotic cells by morphological analysis activated caspase-3 immunohistochemistry. Therefore, results from the present study prove that relatively higher concentrations of ZnPT could cause in an increased apoptosis of hepatocytes in the liver, tubular in kidney gonadal germ cells in the testis and ovarian follicles of gonads in Oryzias javanicus. In conclusion, ZnPT can cause numerous biological effects to targeted and non-targeted organism, especially in areas with intensive shipping and industrial activities. This study was to support the evidence for Oryzias javanicus as an excellent model organism for ecotoxicological studies in aquatic environment of Malaysia.